E-content development and delivery for virtual classroom / Rozita Kadar, Elly Johana Johan and Mohd Saifulnizam Abu Bakar - Kadar, Rozita; Johan, Elly Johana; Abu Bakar, Mohd Saifulnizam (Unit Penerbitan JSKM, 2020)
Virtual Classroom is designed specifically for teachers, professors, and instructors who deliver virtual classes using online meeting platforms. A virtual classroom is a digital replica of a traditional classroom. The teachers teach, and the students learn in real-time, face-to-face but via internet-enabled technology devices. Although there are many fundamental similarities between a traditional classroom education and the online classroom experience, learning through a virtual classroom offers many benefits that traditional classroom doesn't provide. Thus, this paper focuses on the online learning environment, its features, the aspects of the virtual Classroom development and delivery. Also, this paper presents the suitable tools in developing and delivery the e-content for provided the convenient and acceptable environment for learners.